Progressive neurologic and somatic disease in a novel mouse model of human mucopolysaccharidosis type IIIC - Sara Marcó; Anna Pujol; Carles Roca; Sandra Motas; Albert Ribera; Miguel Garcia; Maria Molas; Pilar Villacampa; Cristian S. Melia; Víctor Sánchez; Xavier Sánchez; Joan Bertolin; et al. (The Company of Biologists, 2016)
Mucopolysaccharidosis type IIIC (MPSIIIC) is a severe lysosomal storage disease caused by deficiency in activity of the transmembrane enzyme heparan-α-glucosaminide N-acetyltransferase (HGSNAT) that catalyses the N-acetylation of α-glucosamine residues of heparan sulfate. Enzyme deficiency causes abnormal substrate accumulation in lysosomes, leading to progressive and severe neurodegeneration, somatic pathology and early death. There is no cure for MPSIIIC, and development of new therapies is challenging because of the unfeasibility of cross-correction. In this study, we generated a new mouse model of MPSIIIC by targeted disruption of the Hgsnat gene. Successful targeting left LacZ expression under control of the Hgsnat promoter, allowing investigation into sites of endogenous expression, which was particularly prominent in the CNS, but was also detectable in peripheral organs. Signs of CNS storage pathology, including glycosaminoglycan accumulation, lysosomal distension, lysosomal dysfunction and neuroinflammation were detected in 2-month-old animals and progressed with age. Glycosaminoglycan accumulation and ultrastructural changes were also observed in most somatic organs, but lysosomal pathology seemed most severe in liver. Furthermore, HGSNAT-deficient mice had altered locomotor and exploratory activity and shortened lifespan. Hence, this animal model recapitulates human MPSIIIC and provides a useful tool for the study of disease physiopathology and the development of new therapeutic approaches.